2019
DOI: 10.1021/acs.est.9b02666
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Hydrolysis of Penicillin Antibiotics Mediated by Adsorbed Zinc on Goethite Surfaces

Abstract: The soil environment is an important sink for penicillin antibiotics released from animal manure and wastewater, but the mineral-catalyzed transformation of penicillins in soil has not been well studied. To simulate this environmental process, we systematically investigated the behavior of penicillin G and amoxicillin, the two most widely-used penicillin antibiotics, in the presence of goethite and metal ions. The results demonstrated that Zn ions significantly promoted the hydrolysis of penicillins in goethit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…Furthermore, mineral surfaces can transfer protons to a sorbate as well as offer empty electron orbitals for the reception of bonding electron pairs (Broensted-and Lewis-acid/base functionalities 120 ). Lastly, minerals entirely made of transition metals (such as Fe and Mn oxides) or acting as solid supports for adsorbed transition metals at their surfaces and in interlayers (phyllosilicates) can contribute transition metal specific catalytic functionality 121,122 .…”
Section: [H1] Catalysismentioning
confidence: 99%
“…Furthermore, mineral surfaces can transfer protons to a sorbate as well as offer empty electron orbitals for the reception of bonding electron pairs (Broensted-and Lewis-acid/base functionalities 120 ). Lastly, minerals entirely made of transition metals (such as Fe and Mn oxides) or acting as solid supports for adsorbed transition metals at their surfaces and in interlayers (phyllosilicates) can contribute transition metal specific catalytic functionality 121,122 .…”
Section: [H1] Catalysismentioning
confidence: 99%
“…[6][7][8][9] The β-lactam antibiotics are the most frequently used antibiotics, accounting for more than 50% of the total worldwide antibiotic consumption. [10] In addition, penicillin G (PNL) and amoxicillin (AMX) are among the most commonly used β-lactam antibiotics, which are also the most vulnerable to leakage into the environment. [11] For example, Lu et al investigated 15 target antibiotics in the water of Jiaozhou Bay in China, and the results indicated that the AMX contamination accounted for 44% of the total concentration of antibiotics, which was the highest proportion among the 14 detected antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] As a classical visible light-responsive semiconductor photocatalyst, silver phosphate (Ag 3 PO 4 ) has attracted much attention due to its high photocatalytic oxidation ability. [10,18] However, the defects of poor photostability and unsatisfactory electron-hole separation yield limit the wide application of Ag 3 PO 4 . Therefore, various attempts have been made to overcome the abovementioned drawbacks, such as morphology optimization, [19] ion doping, [20] facet engineering, [21] and heterojunction construction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of photoelectric-Fenton oxidation (PEF) technology for the treatment of ampicillin [ 13 ]; the use of ionizing radiation to degrade penicillin [ 14 ]; and the use of UV/TiO 2 photocatalytic degradation of amoxicillin can achieve amoxicillin degradation. Penicillin can be degraded by nano Fe/Ni (B-Fe/Ni) supported by functional bentonite [ 15 ], Zinc-Loaded materials on a goethite surface [ 16 ], CoFe 2 O 4 @CuS magnetic nanocomposite and so on [ 17 ]. However, these methods are costly, the processing conditions are harsh, and it is difficult to scale up.…”
Section: Introductionmentioning
confidence: 99%